International law - Shaw, Malcolm N. (Malcolm Nathan), 1947- (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2017)
"International Law is the definitive and authoritative text on the subject, offering Shaw's unbeatable combination of clarity of expression and academic rigour and ensuring both understanding and critical analysis in an engaging and authoritative style. Encompassing the leading principles, practice and cases, and retaining and developing the detailed references which encourage and assist the reader in further study, this new edition motivates and challenges students and professionals while remaining accessible and engaging. Fully updated to reflect recent case law and treaty developments, this edition contains an expanded treatment of the relationship between international and domestic law, the principles of international humanitarian law, and international criminal law alongside additional material on international economic law"--
1. The nature and development of international law -- 2. International law today -- 3. Sources -- 4. International law and municipal law -- 5. The Subjects of international law -- 6. The International protection of human rights -- 7. Individual criminal responsibility in international law -- 8. Recognition -- 9. Territory -- 10. The Law of the sea -- 11. Jurisdiction -- 12. Immunities from jurisdiction -- 13. State responsibility -- 14. International environmental law -- 15. The law of treaties --16. State succession -- 17. The settlement of disputes by peaceful means -- 18. The international court of justice -- 19. International Law and the us of force by states -- 20. International humanitarian law --21. The United Nations -- 22. International organisations.
Includes bibliographical references and index.
SOL
Keywords: International law; LAW / International; International law; Law